Evaluation of analgesic (in vivo) activity of Ariflex liniment in comparison with diclofenac gel by acetic acid induced writhing model - Nipanikar, Sanjay U.; Chitlange, Sohan S. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Adverse effects of available medications for osteoarthritis (OA) and rheumatoid arthritis (RA) necessitate development of safer and effective alternative medicinal substitutes. The present study was conducted to evaluate analgesic activity of Ariflex liniment (conceptualized and developed by Ari Healthcare Pvt. Ltd.) in comparison with diclofenac gel by using acetic acid induced writhing model. Methods: Albino mice of either sex weighing 20-25 g were taken and divided into 3 groups with 5 animals in each group, i.e., group 1 (control group), group 2 (diclofenac gel) and group 3 (Ariflex liniment). After 1 hour of topical application of study drugs writhing was induced in mice using intra-peritonial injection of 1% acetic acid in volume of 0.1 ml/10 g body weight. Then the writhing episodes were recorded for 30 minutes and results were noted. Results: In the control group, the total number of writhes were 260±29.73 (mean±S. E. M.). The total number of writhes was 12.17±11.81 (mean ± S. E. M.) in diclofenac group. In Ariflex liniment group, not a single animal felt pain, hence there were no writhes recorded. When compared to control group, the difference in number of writhes was statistically significant. The analgesic activity of Ariflex liniment was found to be superior to that of diclofenac gel used as standard drug. Conclusions: It can be concluded that Ariflex liniment possesses analgesic activity.